A structural topology design method based on principal stress line. (November 2016) - Kwok, Tsz-Ho; Li, Yongqiang; Chen, Yong
Abstract: Topology optimization is an important topic in structural mechanics. One common application is to obtain the optimal distribution of material that maximizes the stiffness of the solution (minimize the compliance). However, as an iterative process, topology optimization of large and complex structures is computationally intensive. The problem becomes even more complicated if the manufacturing constraints are taken into account in the optimization process. In this paper, a novel growth method based on principal stress lines (PSLs) is presented for topology optimization. The PSLs are traced in the design domain along the direction of principal stresses, in which the materials would be located to define the geometry and topology of the structure. Consequently, the optimization problem is converted into a geometric design problem. Compared to previous methods, the computation based on PSLs is fast, and the designer can have explicit control over the number of structural members. In addition, the manufacturing constraints can easily be incorporated. Multiple test cases are given to illustrate the presented method. The PSL-based method is promising for building practical designing tools for various structural applications. Highlights: We develop a new topology design framework using Principal Stress Lines (PSLs). We develop an automatic algorithm based on PSLs for initial structure generation. The PSLs can be used in refining the shape and topology of the structure. We can achieve interactive speed for applications such as design concept exploration.